Benefits of Using Organic Fertilizer for Soil Fertility - Hastirullah Fitrah (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
This paper aims to determine: 1) the Benefits of using organic fertilizers for soil fertility, and 2) Knowing about soil productivity as a medium for supporting plant growth. The research method qualitative approach, which is a scientific approach that produces descriptive data in the form of written words from the narratives of the sources or objects under study. The results of this research is that in the current era of globalization, organic is very important for the development of people who want to live healthily and without damaging the surrounding environment by utilizing natural materials or the remnants of kitchen waste. So farmers are expected to be more aware and creative in the use of organic fertilizers and it is hoped that farmers' income will also increase.